Restoratif Justice In the Perspective of Customary Law: A Solution to the Settlement of Narcotics Crimes Commited by Children - Badu, Lisnawaty Wadju; Kaluku, Julisa Aprilia (Universitas Negeri Gorontalo, 2022)
Restorative Justice is a thought that responds to the development of the criminal justice system by focusing on the needs of the community, where the settlement uses customary law which is something that is very urgent at this time by considering various things besides so that the settlement does not take a long time, but also the parties do not incur large costs and the most important thing is that family relations will remain harmoniously intertwined so as not to leave the problem of